Biomarker‐Responsive Nanosystems for Chronic Disease Theranostics. (23rd November 2022) - Fu, Qinrui; Yu, Leilei; Wang, Yin; Li, Peifeng; Song, Jibin
Abstract: Chronic diseases claim millions of lives every year, and it is of great significance to explore and develop advanced drugs to improve the cure rate of chronic diseases. Nanotheranostics are innovative strategies that enable the integration of diagnostic and therapeutic properties into a single nanosystem. Despite great success in nanotheranostics, their applications of nanotheranostics in nanomedicine are still in their infancy. This is because each disease has its corresponding characteristic pathological microenvironment, which motivates the development of endogenous biomarker‐responsive nanosystems to meet the requirements of diagnosis and treatment. Herein, recent progress is presented in biomarker‐responsive nanosystems and their biomedical applications. First, biomarker‐responsive nanosystems are classified into eight subsections according to the type of chronic diseases, including tumors, cardiovascular diseases, neurological diseases, Wilson's diseases, chronic liver diseases, chronic kidney diseases, diabetes mellitus, and rheumatoid arthritis. In the following, a variety of intriguing applications of biomarkers‐responsive nanosystems are briefly elaborated, such as biosensing, diagnosis, therapy, combined theranostics, and early evaluation of therapy effect, etc. Finally, the challenges and future directions from research to clinical translation of these responsive nanosystems are also presented. Abstract : In this review, the biomarker‐responsive nanomaterials are summarized and reviewed for biomedical applications in various chronic diseases, including cancer, cardiovascular diseases, neurological diseases, Wilson's disease, chronic liver diseases, chronic kidney diseases, diabetes mellitus, and rheumatoid arthritis.